Russia and the Issues of the Korean Peninsula - G. D. Toloraya (Vestnik MGIMO-Universiteta)
The importance of Korean Peninsula in Russian foreign strategy is based on the need to preserve peace and stability in the Russia's Far East "soft underbelly" and to be a part of international efforts to solve the Korean problem, as well as to promote regional economic cooperation. In 1990-s Russia's position on the peninsula weakened, mainly because of the rupture of ties with North Korea, while relations with South Korea were reactive in nature. Rebalancing relations with the two Koreas in 2000-s increased Russia's involvement into Korean settlement, including the 6- party format. Russia/s relations with North Korea are now based on good neighborhood principle, however, they are far from idyllic as Russia disapproves of Pyongyang's behavior, especially its nuclear and missile activities. However to influence the situation more Russia should deepen its ties with the current Pyongyang leadership regardless of how irritating its behavior might be. Relations with the ROK are aimed at becoming strategic, but in reality are limited due to ROK's alliance with the USA. However South Korea has become the third most important economic partner in Asia. Russia is especially interested in three- party projects, such as Trans-Korean railroad (linked to Transsiberan transit way), gas pipeline and electricity grid. However implementation of these project is negatively influenced by the tensions in Korean peninsula. It can be solved only by multilateral efforts for comprehensive solution combining security guarantees for North Korea and its abandonment of nuclear option.